2015
DOI: 10.1111/apt.13148
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of bleeding risk in colonic diverticulosis patients: a long‐term colonoscopy‐based cohort study

Abstract: SUMMARY BackgroundThe natural history of bleeding risk from colonic diverticulosis remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 29 publications
2
33
1
1
Order By: Relevance
“…Arteriosclerosis also plays a role in the pathogenesis patients during the natural history of diverticulosis, and most cases are relatively mild, resolving spontaneously in 75%93% of cases [15,16] . In a casecontrol study in Japan, risk factors for DH included the use of ATDs and NSAIDs, hypertension, diabetes, arteriosclerotic diseases such as ischemic disease mellitus and chronic kidney disease, age ≥ 70 years, obesity [13,15,17,18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arteriosclerosis also plays a role in the pathogenesis patients during the natural history of diverticulosis, and most cases are relatively mild, resolving spontaneously in 75%93% of cases [15,16] . In a casecontrol study in Japan, risk factors for DH included the use of ATDs and NSAIDs, hypertension, diabetes, arteriosclerotic diseases such as ischemic disease mellitus and chronic kidney disease, age ≥ 70 years, obesity [13,15,17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…In a casecontrol study in Japan, risk factors for DH included the use of ATDs and NSAIDs, hypertension, diabetes, arteriosclerotic diseases such as ischemic disease mellitus and chronic kidney disease, age ≥ 70 years, obesity [13,15,17,18] . Our study also found higher rates of use for both ATDs and NSAIDs, higher age and male sex, obesity, smoking, alcohol drinking, and arteriosclerotic diseases in patients with colonic DH compared to those with bleeding from other causes.…”
Section: Discussionmentioning
confidence: 99%
“…The actual incidence of acute diverticulitis was as low as 4.3% over a period of 15 years, challenging the previously reported risk rates [3,11,12]. The study had some limitations in- cluding patient selection, a restrictive definition of outcome, and the lack of ascertainment of diverticular bleeding, another important complication estimated to occur in 3-5% of the patients with diverticulosis [24]. Over an 11-year period, 23 patients (1%) developed rigorously confirmed diverticulitis for an incidence rate of 1.5 per 1,000 patient-years.…”
Section: Natural Historymentioning
confidence: 84%
“…Importantly, the study population consisted of patients with incidental diverticulosis on all-indication colonoscopies and not a well-defined cohort of patients undergoing screening colonoscopy. The second study by Niikura et al [24] from Japan examined the bleeding risk in 1,514 patients with asymptomatic diverticulosis identified over a 12-year period (2001-2013). The median follow-up period was 3.8 years.…”
Section: Natural Historymentioning
confidence: 99%
“…Ezen laesiók találati ará-nyában nem volt különbség a vérző és nem vérző betegpopuláció között, és a gyakoriságok megfelelnek a korábban említett irodalmi adatoknak [35,36,42,43]. Bár a diverticulumokból eredő vérzés az akut alsó GI-vérzé-sek leggyakoribb oka (24-47%), a diverticulumok csak igen csekély hányadából származik vérzés [47,48]. A colorectalis daganatok találati arányában már szignifikáns különbség adódott vérző és nem vérző betegcsoportok között (13,2% vs. 4,3%).…”
Section: Megbeszélésunclassified